2017
DOI: 10.1002/2017ja024067
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence characteristics of relativistic electron microbursts from SAMPEX observations

Abstract: We study the occurrence of relativistic microbursts observed by the Solar Anomalous Magnetospheric Particle Explorer (SAMPEX) satellite. An algorithm is used to identify 193,694 relativistic microbursts in the > 1.05 MeV electron fluxes occurring across the time period 23 August 1996 to 11 August 2007, nearly a full solar cycle. Our observations are normalized to provide the change in absolute occurrence rates with various parameters. We find that relativistic microbursts are mostly confined to the outer radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 42 publications
(139 reference statements)
13
67
0
Order By: Relevance
“…We now investigate how the mean intensity of relativistic microbursts changes under different levels of geomagnetic activity. In order to remain consistent with earlier work (e.g., Li et al, ; Douma et al, ), we have defined three levels of geomagnetic activity based on AE * (the mean of AE over the previous 1 hr); quiet corresponds to AE * ≤ 100 nT, disturbed corresponds to 100 < AE * ≤ 300 nT, and active corresponds to AE * > 300 nT. However, our large relativistic microburst data set allows us to also extend these well used AE * ranges to include higher geomagnetic activity; intense conditions correspond to AE * > 550 nT and extreme conditions correspond to AE * > 750 nT.…”
Section: Flux Magnitude Characteristicsmentioning
confidence: 81%
See 1 more Smart Citation
“…We now investigate how the mean intensity of relativistic microbursts changes under different levels of geomagnetic activity. In order to remain consistent with earlier work (e.g., Li et al, ; Douma et al, ), we have defined three levels of geomagnetic activity based on AE * (the mean of AE over the previous 1 hr); quiet corresponds to AE * ≤ 100 nT, disturbed corresponds to 100 < AE * ≤ 300 nT, and active corresponds to AE * > 300 nT. However, our large relativistic microburst data set allows us to also extend these well used AE * ranges to include higher geomagnetic activity; intense conditions correspond to AE * > 550 nT and extreme conditions correspond to AE * > 750 nT.…”
Section: Flux Magnitude Characteristicsmentioning
confidence: 81%
“…As we move outward from the plasmapause in Figure a we observe the largest mean intensity for the relativistic microbursts occurs at 1.25 L from the plasmapause with a mean intensity of 1,484 (MeV cm 2 sr s) −1 . This L band is ∼1 L closer to the plasmapause than the L band with the most frequent microburst activity (Douma et al, ). Moving inward from the plasmapause we note that the microburst intensity appears to increase.…”
Section: Flux Magnitude Characteristicsmentioning
confidence: 87%
“…In order to describe the characteristic precipitation in these events, we utilize the relativistic microburst data set derived from Solar, Anomalous, and Magnetospheric Particle Explorer (SAMPEX) Heavy Ion Large Telescope (HILT), recently reported in Douma et al (). We employ the O'Brien et al () algorithm which was updated by Blum et al () to include the microburst intensity.…”
Section: Methodsmentioning
confidence: 99%
“…SAMPEX observed the relativistic microburst event while at an average IGRF L of 5.8 (the event was seen from L = 5.3–6.3). Figure a presents the > 1 MeV flux observed by SAMPEX during the time of this microburst event, with the microburst algorithm triggers (described in more detail in Douma et al, ) indicated by the red crosses. This microburst event consists of 16 individual microbursts detected by the algorithm, occurring during an A E index value of 298 nT ( D s t of −11 nT, and K p of 3).…”
Section: Case Studiesmentioning
confidence: 99%